MODEL LATIHAN FOREHAND SMASH BULUTANGKIS BAGI ATLET PB SEMERU PUGER KABUPATEN JEMBER USIA 12–15 TAHUN - Vernando, Yonatan Teguh; Adi, Sapto; Wahyudi, Usman (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2017)
Abstract: Skills forehand smash athletes Semeru Puger PB Jember age 12-15 years is still not good. One of exercise to improve the forehand smash is using a model of exercise. The aim of this research was to improve the skills of athletes forehand smash Semeru Puger PB Jember aged 12-15 years. The study design used is Sports Action Research that leads to a research experiment. Based on the results of data analysts, models forehand smash badminton exercise can boost the skills forehand smash badminton athletes PB Semeru. So, using the model of exercise forehand smash badminton, athlete skill Semeru Puger PB Jember age 12-15 years in doing forehand smash can be increased. Key words: forehand smash, model exercise, badminton. Abstrak: Keterampilan pukulan forehand smash atlet PB Semeru Puger Kabupaten Jember usia 12-15 tahun masih kurang baik. Salah satu latihan untuk meningkatkan pukulan forehand smash adalah menggunakan model latihan. Tujuan dari penelitian ini adalah untuk meningkatkan keterampilan forehand smash atlet PB Semeru Puger Kabupaten Jember usia 12-15 tahun. Rancangan penelitian yang dipakai adalah penelitian tindakan olahraga yang menjurus ke penelitian eksperimen. Berdasarkan hasil analis data, model latihan forehand smash bulutangkis dapat meingkatkan keterampilan forehand smash bulutangkis atlet PB Semeru. Jadi, dengan menggunakan model latihan forehand smash bulutangkis, keterampilan atlet PB Semeru Puger Kabupaten Jember usia 12-15 tahun dalam melakukan pukulan forehand smash dapat meningkat. Kata kunci: forehand smash, model latihan, bulutangkis.